Invasion of Chicken Intestinal Cells Is Higher for Enterococcus cecorum Lesion Strains Compared to Cloacal Strains in an Organoid Model - Lonneke Vervelde; Thijs T. M. Manders; Samira Kammourieh; Jeanine Wiegel (Microorganisms)
Some strains of Enterococcus cecorum can cause spondylitis and bacterial osteomyelitis. Translocation and bacteremia are pivotal to the pathogenesis and clinical disease. Virulence typing to distinguish extra-intestinal disease of lesion from cloacal strains remains difficult. We investigated if organoids can be applied to differentiate between E. cecorum strains that are more or less virulent. Floating chicken intestinal organoids combine the complex cell system of the gut with an easily accessible apical-out orientation. The organoids were treated with four E. cecorum strains that differ in original isolation, lesion, or cloacal, and bacterial load was determined after 3 and 6 h by quantitative PCR and bacterial plating. Independent of the inoculum dose or time post inoculation, DNA levels of E. cecorum marginally differed between the strains. To determine if this was caused by adherence of bacteria to the epithelial cells, an invasion assay was developed. The organoids were inoculated with the different E. cecorum strains and after 3 or 6 h treated with an antimicrobial mixture, lysed, and quantified by bacterial plate counting. Significantly higher (p < 0.0001) numbers of bacteria isolated from lesions invaded the organoids compared to cloacal strains in a dose-dependent manner. Higher numbers of bacteria isolated from lesions invaded the organoids compared to cloacal strains in a dose-dependent manner. This study is a major step in the development of a model to study the interaction between E. cecorum and the chicken host and a model to test novel intervention strategies to prevent translocation of bacteria.